Creating Inspiring Learning Environments by means of Digital Technologies: A Case Study of the Effectiveness of WhatsApp in Music Education - Michele Della Ventura (European Alliance for Innovation (EAI), 2017)
One of the most interesting challenges that many schools are facing today is the introduction of the most recent digital technologies in the learning process. These technologies also turn out to be efficient for the students in terms of motivation. Motivation and the nature of the learning experience are important factors for all students, but particularly for students with dyslexia. This research paper explores the effectiveness of using mobile technologies to support a course titled "Sound Recording" in Music Technology. Specifically, it discusses the effects of WhatsApp mobile learning activities guided by activity theory on students' knowledge management. Results showed that students with dyslexia compensated for their processing deficits by relying on learning strategies and help seeking.